FACTORES CONSTITUCIONALES QUE DETERMINAN LA INADECUADA APLICACIÓN DEL PROCEDIMIENTO DE VACANCIA EN LOS CONSEJOS REGIONALES Y MUNICIPALES - Chero Arroyo, Roberto (2017)
This thesis called "the constitutional factors that determine the inadequate application of the procedure of vacancy in the regional and municipal councils", has as an object of research the vacancy procedure regulated in article 15, literal g regional and municipal councils) and article 30 of the law Nº 27867, the organic law of regional Governments and in article 9 literal 10) , articles 22 and 23 of the Act No. 27972, organic law of municipalities, respectively, for the purpose of determining the constitutional factors that determine the inadequate application of the procedure of vacancy in the regional and municipal councils. So, to comply with said purposes has been used as population and sample sentences of the national jury of elections in terms of vacancy and regional councillors, mayors and municipal freedom regional advisors, surveys has been used scientific, logical, legal method and has been used in the documentary analysis and survey techniques. The main results that were found in this research were the following: the ignorance and failure to observe due process and right to defence does not constitute constitutional factors that determine the inadequate application of the procedure of vacancy in the regional councils. The lack of due process and right to defense is constitutional factor that determines the inadequate application of the procedure of vacancy in the provincial councils, but not failure. Ignorance and neglect of due process and the rights of the defence are constitutional factors that determine the inadequate application of the procedure of vacancy in the District Councils